A Pyroxenic View on Magma Hybridization and Crystallization at Popocatépetl Volcano, Mexico - Mangler, Martin F.; Petrone, Chiara M.; Hill, Samuel; Delgado-Granados, Hugo; Prytulak, Julie (Frontiers in Earth Science, 2020)
The Popocatépetl Volcanic Complex (PVC) is an active arc volcano located in Central Mexico, 70 km southeast of Mexico City. Current models of the PVC’s plumbing system and magma petrogenesis are largely based on the study of isolated Plinian eruptions in the past 23.5 ka and present-day Vulcanian activity, while voluminous effusive summit and flank eruptions remain underrepresented. Here, we present a detailed petrological characterisation focussed on ortho- and clinopyroxene in six effusive flank eruptions and two Plinian eruptions of the PVC during the last ~14.1 ka. Texturally and compositionally defined pyroxene populations facilitate novel approaches to constraining magmatic temperatures and deconvolving crystallisation histories. At least two inter-connected magma reservoirs are present in the mid-to upper crust beneath the PVC: (1) a magnesian andesitic reservoir crystallising high-Mg orthopyroxene (Mg# 79–90) + clinopyroxene (Mg# 82–91) + Cr-spinel ± sulfide at temperatures of 1000–1115°C, and (2) a more evolved, shallower magma reservoir crystallising plagioclase (An50–28) + low-Mg orthopyroxene (Mg# 56–71) + clinopyroxene (Mg# 64–79) + magnetite + ilmenite + apatite ± sulfide at a long-term storage temperature of ~970°C. These mid- to upper crustal magma reservoirs are periodically recharged with a hydrous, high-Mg basaltic mantle melt that crystallised fosteritic olivine (Fo82–89) + Cr-spinel + low-Ca clinopyroxene with elevated Al2O3 (≤6 wt. %) in the lower- to mid-crust at 1080–1220°C. Short- and long-term melt and crystal hybridisation is the primary driver producing the diverse crystal cargo and restricted whole-rock compositions that characterise effusive and explosive eruptions of the PVC in the last ~14.1 ka. Injections of the magnesian andesite into the evolved reservoir produce transient melts crystallising hybrid rims around pre-existing pyroxene and plagioclase crystals. Crystals are subsequently stored in a heterogeneous mush comprising multiple generations of crystals dominated by injected pyroxene of mafic origin. The majority of mafic pyroxene crystals (≤78 %) were stored in the evolved reservoir for centuries to millennia, resulting in near-complete diffusive overprinting of the mafic compositions. Magma injections from depth frequently remobilise the crystal mush and may lead to effusive and explosive eruptions of hybridised PVC andesites and dacites.